Bone marrow transplantation for chronic myeloid leukemia in the tirosinekinase inhibithors era: a Bahia´s center experience - Pallotta Filho, Ronald Sérgio; Paula, Gerson Geraldo de; Lima Filho, Edson Ferreira; Giuliani, Rosane (Brazilian Journal of Transplantation, 2010)
Introduction: Chronic myeloid leukemia accounts for approximately 15% of all leukemias. It is a chronic clonal myeloproliferative disorder that can occur at any age, but its peak incidence is in individuals between the sixth and seventh decades of life. It classically evolves in three stages: chronic, accelerated and blast crisis. Diagnosis is based on clinical findings in peripheral blood and bone marrow examination with cytogenetic analysis and molecular biology. Currently, the two most commonly used therapies are tyrosine kinase inhibitors like imatinib mesylate, which revolutionized the treatment of the disease and transplantation of hematopoietic progenitor cells, considered by many authors the only curative method. Purpose: The objective of this study is to describe the epidemiological profile of patients treated for chronic myeloid leukemia comparing the response to treatment in a reference center in Bahia, Northeastern Region of Brazil. Methods: We conducted an observational, descriptive, retrospective cross-sectional study, in which 73 records were analyzed. Results: The median age was 39 years, predominantly male (69.9%) and nonwhite (64.4%). The stage was the predominant clinical disease (78.1%), followed by accelerated (19.2%) and blast crisis (2.7%). The overall survival rates in groups treated with imatinib mesylate and transplants accounted for 87.5% and 43.1% respectively. Survival rates free of disease progression for same groups were 63.2% and 28.9% respectively. Conclusion: It can be concluded that male patients with median age of 39 years, nonwhites and diagnosed in chronic phase are the predominant epidemiological profile of patients treated in a reference center of Salvador. Likewise, upon analyzing the curves of overall survival and progression-free disease, it is concluded that treatment with imatinib mesylate has better effective, decreasing the mortality compared to transplantation.